Nathalie Sarraute's Between Life and Death: Androgyny and the Creative Process - Bettina L. Knapp (Studies in 20th & 21st Century Literature, 1987)
Nathalie Sarraute's Between Life and Death deals with the creative process, from the uncreated work of art embedded in the prima materia to its completion in the book. The Writer, the focus of Sarraute's attention, takes the reader through the multiple stages of his literary trajectory: the struggle involved in the transmutation of the amorphous word into the concrete glyph on the blank sheet of paper; the pain and anguish accompanying the birth of the created work, alluded to as the "thing" or the "object"; the attitude of the successful Writer, who postures and panders to his public, and the rebirth of the creative élan following an inner vision. How does the Writer, like the ancient rates inject "life" into what has previously been "dead," or uncreated: the written word? How does the course of the word from the uncreated to concretion in the empirical world affect both the Writer—as androgyne—and the reader during the happenings in Between Life and Death?
Keywords: Nathalie Sarraute; Between Life and Death; creative process; art; prima materia; writer; literary trajectory; amorphous; word; transmutation; glyph; pain; birth; thing; object; successful Writer; rebirth; creative; élan; written word; life; death; dead